Adsorption of Phenols from Different Solvents on Graphene: Semi-Empirical Quantum Mechanical Calculations - Pablo Húmpola; Héctor S. Odetti; Alberto G. Albesa; José L. Vicente (Adsorption Science & Technology)
The adsorption of phenol from aqueous solutions on carbon surfaces is discussed from different theoretical points of view, such as Monte–Carlo simulations, semi-empirical calculations, density functional theory and molecular dynamics. We performed a quantitative analysis of the adsorption of aromatics in general, and phenolic compounds in particular, through semi-empirical quantum mechanical calculations using different approaches. Our results raise doubts that phenol is primarily adsorbed in flat position on the graphene layers, and consequently whether the adsorption forces are controlled by π–π dispersion interactions between the aromatic ring of phenol and the graphene layer structure. Based on the results of quantum mechanical calculations (carried out through various approaches), we conclude that neither surface oxidation nor the presence of a polarizable solvent is consistent with the claim that π–π interactions are dominant in the adsorption of phenolic compounds on graphite.